Learning From Each Other in the Management of Natural Disaster and COVID-19 Pandemic: A Case Study in Taiwan - Wang, Hsiao-Wen; Chen, Guan-Wei; Lee, Wei-Lin; You, Shuei-Huei; Li, Chia-Wen; Jang, Jiun-Huei; Shieh, Chjeng-Lun (Frontiers in Public Health, 2021)
In response to the COVID-19 pandemic, Taiwan has been one of the best performers in the world with extremely low infections and deaths. This success can be attributed to the long experiences dealing with natural disasters and communicable diseases. However, with different disastrous characteristics, the disaster management systems for communicable diseases and natural disasters are very different in terms of laws, plans, frameworks, and emergency operations. Taking the response to COVID-19 pandemic as a study subject, we found that disaster management for communicable diseases can be improved through a comparison with natural disasters, and vice versa. First, having wider and longer impacts than natural disasters, the plans and framework for communicable diseases in Taiwan focus more on national and regional scales. Local governments would need more capacity support including budgets and training to conduct investigations and quarantine during the COVID-19 pandemic. Second, for quick response, the emergency operation for communicable diseases was designed to be more flexible than that for natural disasters by giving the commander more authority to adjust to the circumstances. The commanding system requires a more objective consultation group to prevent arbitrary decisions against the COVID-19 pandemic. Finally, risk governance is important for communicable diseases as well as for natural disasters. Additional efforts should be made to enhance vulnerability assessment, disaster reduction, and risk communication for shaping responses and policies in an efficient and coordinating way.